Building on Strengths While Addressing Barriers: Career Interventions in Rural Appalachian Communities - Gibbons, Melinda M. (J Career Dev, 2019)
This article describes a model for developing culturally-sensitive career education programs, framed from an ecological contextual understanding (Bronfenbrenner, 1979). This framework allows career practitioners to build on cultural strengths and values to meet the career education needs of diverse communities. To illustrate the application of this model, we describe the cultural context of rural Appalachia and offer theoretically-framed ideas of how to meet the population’s career education needs.